2013
DOI: 10.1117/12.2007701
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticle enhancement of radiation cytotoxicity

Abstract: Iron oxide nanoparticles (IONPs) have been investigated as a promising means for inducing tumor cell-specific hyperthermia. Although the ability to generate and use nanoparticles that are biocompatible, tumor specific, and have the ability to produce adequate cytotoxic heat is very promising, significant preclinical and clinical development will be required for clinical efficacy. At this time it appears using IONP-induced hyperthermia as an adjunct to conventional cancer therapeutics, rather than as an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
4
1
Order By: Relevance
“…Remarkably, the equivalent iron concentration in the nanoMOFs used in this study was much lower than the one reported in previous studies with other iron oxide NPs (nanoMOFs contain 56 μM Fe compared to iron oxide NPs containing 3.6 mM ∼17.9 mM Fe). Moreover, the incubation time was also much shorter (6 h for nanoMOFs in comparison with 72 h for iron oxide NPs). The amount of Fe internalized in cells in the case of iron oxide NPs reached up to 40 pg/cell, whereas in this study, it was only 1.5 pg/cell.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Remarkably, the equivalent iron concentration in the nanoMOFs used in this study was much lower than the one reported in previous studies with other iron oxide NPs (nanoMOFs contain 56 μM Fe compared to iron oxide NPs containing 3.6 mM ∼17.9 mM Fe). Moreover, the incubation time was also much shorter (6 h for nanoMOFs in comparison with 72 h for iron oxide NPs). The amount of Fe internalized in cells in the case of iron oxide NPs reached up to 40 pg/cell, whereas in this study, it was only 1.5 pg/cell.…”
Section: Resultscontrasting
confidence: 74%
“…This is comparable to the effects observed by Mazur et al . with iron oxide NPs, showing DEF (1‐4 Gy) values in the range of 1.1–1.6 . This clearly indicates that nanoMOFs enhance radiation effects.…”
Section: Resultsmentioning
confidence: 81%
“…In this study, the effect of exposure time on the toxicity in the exposed cells was investigated, and the results indicated that by increasing exposure time, the rate of toxicity was higher because of the higher ROS generation, mitochondrial permeability, and decreased intracellular glutathione content. In other studies, exposure time also has been presented as an effective factor in cell uptake and increased toxicity (Pauluhn, 2012; Mazur et al, 2013). The failure of the cell cleansing mechanisms followed by increased exposure time could be a factor for a higher toxicity rate reported in some other studies (Bouallegui et al, 2018; Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up studies also provided evidence for this promising application of IONs 126 - 128 . It was also reported that IONs were able to enhance radiation cytotoxicity of γ-rays 129 . In addition to IONs, other types of iron based-nanoparticles have shown radiosensitizing effects 130 .…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 95%